Quality of Metal Deposited Flux Cored Wire with the System Fe-C-Si-Mn-Cr-Mo-Ni-V-Co; Key Engineering Materials; Vol. 736 : Materials and their Application - Gusev A. I. Aleksandr Igorevich; Kozyrev N. A. Nikolay Anatoljevich; Osetkovsky I. A. Ivan Vasiljevich; Kozyreva O. A. Olga Anatoljevna; Valuev D. V. Denis Viktorovich (2017, 2017)
Title screen